A Study to Determine the Perinatal Outcome in Isolated Oligohydramnios at Term Pregnancy - Rabeea Sadaf, Saman Muddassar, Nasreen Kishwar, Umaima Farhad, Samreen, Laila, Shazia Khattak, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: A Study to Determine the Perinatal Outcome in Isolated Oligohydramnios at Term Pregnancy Study Design: A cross-sectional study Place and Duration: Department of Gynecology and Obstetrics, Hayatabad Medical Complex from October 2022 to March 2023 Methodology: Our sample size was 250 which were divided into 1:1 including 125 cases with isolated oligohydramnios and 125 control cases. Patients with chronic medical disorders and having fetal anomalies or IUGR were excluded. The mode of delivery was noted. Neonatal outcomes in the form of Apgar score, baby weight and need for NICU were noted. Results: The cases with isolated oligohydramnios were associated with an increased incidence of CTG changes, meconium-stained amniotic fluid and the cesarean section as compared to women with normal amount of amniotic fluid. There was no difference between the cases and controls as regards duration of labor, need for oxytocin augmentation, need for neonatal resuscitation, APGAR score at 5 minutes, NICU admission birth weight of neonates or incidence of LSCS for fetal distress. A significant association (OR=1.85, P<0.001) was found between caesarean section in mothers with oligohydramnios compared to controls. Conclusion: Our study found increase cesarean section rate due to CTG changes and meconium stained liquor in isolated oligohydramnios. However neonatal outcome in the form of birth weight, Apgar score and NICU admission was same for both cases and control. Keywords: Oligohydramnios, Perinatal, Term Pregnancy